What Matters for Job Finding and Separation in the Long Run? : Evidence from Labor Market Dynamics in New Zealand - Zheng, Guanyu (IMF Working Papers; Working Paper ;, 2022)
We use the novel anonymized Household Labour Force Survey (HLFS) microdata to analyze job finding rates and job separation rates in New Zealand. We find that individual characteristics, including age, gender, ethnicity and education have a significant impact on job finding and separation rates, even after controlling for other factors. We use a decomposition approach to analyze how the effects of individual characteristics on job finding and separation rates contribute to heterogeneity in employment outcomes. Overall, we find that higher separation rates of young workers play a disproportionate role in explaining heterogeneity of employment outcomes across age groups, while differences in finding rates are somewhat more important in explaining differences by education level. Both finding and separation rate differences are important in explaining differences across ethnicities. We also find some heterogeneous response of worker groups to business cycle after controlling for other factors. The results underscore the importance of well-targeted labor market support policies.